Various Configurations of Au@Pt Nanostructures on Modified Electrochemical Sensors for H2O2 Detection - Mostafiz, Bahar; Suni, Johanna; De Jesus Cabrera; Edna; Mathews, Nidhin George; Gogoi, Rituporn; Mohanty, Gaurav; Sharma, Vipul; Peltola, Emilia (American Chemical Society (ACS), 2025)
Hydrogen peroxide (H2O2) is a vital metabolite involved in numerous biological processes, with physiological concentrations in humans ranging from 1 to 50 μM. Its rapid production, utilization, and decomposition make accurate low-concentration detection challenging. Although precious metals such as gold and platinum are effective for H2O2 detection, their high cost and limited availability necessitate alternative strategies. Nanostructuring these materials into core–shell nanorods (their size ∼ 40 nm in length) offers a sustainable, efficient solution by reducing material usage while enhancing performance. In this study, we modified glassy carbon electrodes with two types of Au@Pt nanorods (NR) for H2O2’s cyclic voltammetric and chronoamperometric detection: plain-surfaced (Smooth) and appendaged-surfaced (Hairy). Both sensors exhibit rapid stabilization, achieving reliable measurements within 5 s, suitable for capturing the volatile nature of H2O2. The Hairy NRs demonstrate superior performance, attributed to the increased presence of catalytically active Pt(0) compared to the less active Pt(II) in Smooth NRs. This difference in oxidation states, combined with the enhanced surface geometry of Hairy NRs, results in faster kinetics, a wider linear detection range (500 nM–50 μM vs 1–50 μM), lower detection limit (189 nM vs 370 nM), and nearly double sensitivity. To simulate physiological conditions, we assessed oxygen interference and evaluated performance in biologically relevant environments. Cell viability tests were conducted to determine the nanoparticles’ toxicity toward neuroblastic cells. These findings support further development of modified Au@Pt nanorod electrodes for in vivo and in vitro applications. With rapid response times, favorable detection limits, and high sensitivity, these sensors are promising for biomedical diagnostics, environmental monitoring, and studying neurotransmitters like glutamate.